EARLY PREGNANCY DIAGNOSIS IN WATER BUFFALOES USING TRANSRECTAL ULTRASONOGRAPHY - AWASTHl, M K; KHARE, ABHISHEK; KAVANI, F S; SIDDIQUEE, G M; DHAMI, A J (The Indian Journal of Animal Reproduction, 2011)
The objective of present study was to evaluate the accuracy of simplified technique of pregnancy diagnosis at an early stage using transrectal ultrasonography (TRUS) in milch water buffaloes. The diagnosis of pregnancy was primarily based on visualization of embryonic vesicle and observation of embryo was compromised with detection of embryonic vesicle for determination of pregnancy. The uterine horn ipsilateral to ovary bearing corpus luteum (CL) was scanned through serial ultrasound scanning on Days 23, 25, 28 and 30 post-service in freshly bred Mehsana buffaloes (n=40) for pregnancy diagnosis. Sensitivity and negative predictive value of early pregnancy diagnosis was 100% on each day of TRUS, but the specificity was lower on Days 23 and 25 than Days 28 and 30. Specificity (93.3% ), positive predictive value (96.1 % ) and accuracy (97 .5%) were maximum and similar on Days 28 and 30 post-service. The embryo was first observed on 26.33 ± 0.52 (mean± SE) days post-service, while the heartbeats were first detected on 29.25 ± 0.36 days post-service; however, embryo could be visualized in 17 out of 25 pregnant animals. The mean length and diameter of embryonic vesicle were recorded as 15.5 ± 0.94 and 6.5 ± 0.55 mm on Day 23, which increased to 24.1 ± 1.07 and 9.6 ± 0.77 mm, respectively, on Day 30 post-service. It is concluded that detection of early pregnancy in buffaloes may be accomplished on and after Day 28 post-service through TRUS with positive predictive value and diagnostic accuracy over 96% and observation of embryo may be compromised with detection of embryonic vesicle for confirmation of pregnancy during early stage.